Ratnakūṭa Studies: Volume I - Felbur, Rafal (Buddhist Open Philology Project Series, 2024)
This volume initiates a new series dedicated to offering state-of-the-art critical editions, translations, and studies of Buddhist scriptures, seeking to set a standard for the presentation of Buddhist literature analogous to that in Biblical Studies and in Classics